2010
DOI: 10.1007/s00253-010-2988-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a GH62 α-l-arabinofuranosidase specific for arabinoxylan produced by Penicillium chrysogenum

Abstract: An arabinoxylan arabinofuranohydrolase (AXS5) was purified from the culture filtrate of Penicillium chrysogenum 31B. A cDNA encoding AXS5 (axs5) was isolated by in vitro cloning using the N-terminal amino acid sequence of the native enzyme as a starting point. The deduced amino acid sequence of the axs5 gene has high similarities with those of arabinoxylan arabinofuranohydrolases of Aspergillus niger, Aspergillus tubingensis, and Aspergillus sojae. Module sequence analysis revealed that a "Glyco_hydro_62" was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 31 publications
4
32
0
Order By: Relevance
“…In fact, in our previous study, we showed that xylooligosaccharides can reversibly bind in the xylan-binding pocket of CBM13 linked to ␤-1,4-xylanase using decorated xylooligosaccharides (56). Moreover, cleavage of arabinofuranosyl side chains linked to O2 and O3 of single-substituted xylose residues in arabinoxylan by GH62 arabinofuranosidase was previously reported (49).…”
Section: Catalytic Mechanisms and Substrate Specificities Of Gh62 Enzmentioning
confidence: 98%
“…In fact, in our previous study, we showed that xylooligosaccharides can reversibly bind in the xylan-binding pocket of CBM13 linked to ␤-1,4-xylanase using decorated xylooligosaccharides (56). Moreover, cleavage of arabinofuranosyl side chains linked to O2 and O3 of single-substituted xylose residues in arabinoxylan by GH62 arabinofuranosidase was previously reported (49).…”
Section: Catalytic Mechanisms and Substrate Specificities Of Gh62 Enzmentioning
confidence: 98%
“…Early on product profiles indicated that SlAbf62A hydrolyzed AXOS of DP 2 6 (unknown Araf substitution patterns) (Vincent et al, 1997). 1 H NMR analysis showed Penicillium chrysogenum GH62 ABF (PcAbf62A-m2,3) hydrolyzed -L-1,3 faster than -8 L-1,2 linked Araf from singly substituted Xylp in AX (Lange et al, 2006;Sakamoto et al, 2010) and that AnAbf62A-m2,3 released -1,3 three times faster than -1,2 linked Araf from a 1:1 XA 2 XX+XA 3 XX mixture (Wilkens et al, 2016). Using different AXOS substrates ScAbf62A, PfAbf62A-m2,3 and PfAbf62C-m2,3 were demonstrated to hydrolyze singly -1,2 and -1,3 linked…”
Section: Activity On Arabinoxylan and Arabinoxylooligosaccharidesmentioning
confidence: 99%
“…To date, all of the biochemically characterized GH62 are arabinoxylan ␣-L-arabinofuranohydrolases, in as much that they specifically cleave either ␣-1,2-or ␣-1,3-L-arabinofuranosidic linkages in arabinoxylans (11). In the case of GH62 ␣-Larabinofuranosidases from Penicillium chrysogenum and Penicillium funiculosum, 1 H NMR and hydrolytic fingerprinting revealed that these enzymes cleave ␣-1,2-or ␣-1,3-bonds that specifically link arabinofuranosyl moieties to single-substituted D-xylosyl residues in arabinoxylan (12)(13)(14).…”
mentioning
confidence: 99%